First absolute chronologies of neolithic and bronze age settlements at Lake Ohrid based on dendrochronology and radiocarbon dating. (August 2021) - Hafner, Albert; Reich, Johannes; Ballmer, Ariane; Bolliger, Matthias; Antolín, Ferran; Charles, Mike; Emmenegger, Lea; Fandré, Josianne; Francuz, John; Gobet, Erika; Hostettler, Marco; Lotter, André F.; et al.
Highlights: The prehistoric site of Ploča Mičov Grad shows outstanding preservation conditions. The analyzed wood provides well replicated dendrochronological mean curves. Several construction phases of Neolithic and Bronze Age settlements are evidenced. Abstract: Specialized and systematic underwater fieldwork at the prehistoric site of Ploča Mičov Grad at Gradište (North Macedonia) on the eastern shore of Lake Ohrid was undertaken in 2018 and 2019. It has substantiated the archeological site's outstanding preservation condition, and furthermore proven the numerous construction timbers' suitability for dendrochronological analysis. Dendrochronological analysis on archaeological timbers was applied, combined with radiocarbon dating. Bayesian radiocarbon modeling allowed to 'wiggle match' the dendrochronological mean curves, i.e. allowed the precise chronological anchoring of 'floating' tree-ring sequences. Furthermore, radiocarbon dates of plant remains from the site's main archaeological layer are statistically evaluated. Based on the new findings, the strikingly high density of wooden piles at the site can be attributed to several construction phases of Neolithic (middle of 5th millennium BC) and Bronze Age (2nd millennium BC: 1800, 1400 and 1300 BCE) settlements. Intense settlement activity is furthermore evidenced by a cultural layer of mainly organic material under the lakebed up to 1.7 m in thickness, which accumulated during the Neolithic occupation of the bay in the middle of the 5th millennium BC. The presented research enables precise absolute dating of a series of settlement phases at Ploča Mičov Grad from the Neolithic and the Bronze Age, and hence provides important reference points for an absolute chronological framework for the prehistory of the southwestern Balkans. The investigations underline the potential of future research on waterlogged prehistoric settlements in the region.